Técnicas de aprendizaje interactivo para la comprensión de textos en las niñas y niños del quinto año de Educación General Básica de la Escuela de Educación Básica García Moreno, del Cantón Riobamba, provincia de Chimborazo, período 2017 - 2018 - Guzmán Guacho, Cristhian Andrés (2018)
The educational establishments currently have to use appropriately interactive tools that stimulate curiosity, in the case of reading, these should be used to bring students closer to reading; therefore, the present investigation had as objective: to determine the interactive learning techniques that favor the comprehension of texts, being these, tools that allow the students to participate with the new material as they learn, to process the information and to cement their knowledge, generating the understanding of texts. In accordance with the objectives set out, the benefit of interactive learning techniques in the comprehension of texts was identified by providing the student with strategies such as: brainstorming, crossword puzzles, word searches, debates, etc .; These activities were carried out in software such as: Educaplay, Educima, Ardora, among others. The methodology used was descriptive and observation cards were used to collect data; from the results it was concluded that the activities applied in each of the software allowed the active participation of the students and the development of schematization skills, synthesis of information; that is why it is recommended to apply interactive techniques with the aim of contributing to the active participation of students.